A Novel Approach for Data Hiding by integrating Steganography & Extended Visual Cryptography (International Journal of Engineering and Computer Science, 2014)
This paper proposes a novel approach for transmitting secret data securely by integrating steganographic method & visual cryptography. Steganography is the art & science of hiding data in the images. In the older age, our ancestors had also used the steganography. For eg., they use invisible ink, tattooing etc. for hiding secret information. In the digital age, secret data is hidden within the image, file, audio, video, text etc. Cryptography is the art & science of converting plain text or data into an unreadable form which is called as cipher text. The advantage of steganography over cryptography is that in cryptography everybody knows about the existence of the message but in steganography only the sender & the receiver knows about the existence of the message so it does not attract unwanted attention. Although there has been an extensive research in the past related to cryptography & steganography but neither of them provide enough security. So the proposed system combines steganography & visual cryptography for hiding data.